Localized and Systemic Immune Response in Human Reproductive Tract - Gudisa, Rajendra; Goyal, Kapil; Gupta, Parakriti; Singh, Mini P. (Frontiers in Cellular and Infection Microbiology, 2021)
Sexually transmitted infections (STIs) are one of the significant causes of morbidity and mortality among adolescents and adults across the globe and encompass all the infections transmitted via person-to-person sexual contact. In spite of the widespread approach being used, STIs remain under-reported and many infections have taken an epidemic turn. The biggest roadblock in this is the unraveled basis of immunopathology of these infections, hindering the discovery of potential targets for immunization. Thereby, it is of utmost significance to decipher the hidden basis of these STIs to control the increasing epidemic of less commonly studied STIs. A complex interplay between innate immune defenses, with resident microbiota and mucosal immune response serves as the basis of therapeutic approaches, by targeting the vital steps of this dynamic interaction. The characterization of pathogen-specific antibodies to significant immunogenic molecules may divulge the conceivable protective effects.